Global burden and regional disparities of rheumatoid arthritis among the working-age population: A comprehensive analysis from 1990 to 2021 with projections to 2040 - Jun Li; Zhiyong Li; Chengluo Hao; Xiangrui Chen (PLoS ONE, 2025)
Objective To evaluate the age-standardized incidence (ASIR), prevalence (ASPR), death (ASDR), and disability-adjusted life year (DALY) rates of rheumatoid arthritis (RA) among the working-age population from 1990 to 2021. Methods The data is sourced from the Global Burden of Disease 2021. Estimated annual percentage change (EAPC) was utilized to assess temporal trends. Decomposition analysis was conducted to identify the driving factors underlying burden changes. The Slope Index of Inequality and the Concentration Index were employed to evaluate cross-country inequalities. Results In 2021, there were 11.88 million cases of RA in the working-age population globally and an ASPR of 222.68 per 100,000 population. The ASIR was 14.09 per 100,000 population (95% uncertainty interval [UI]: 8.97 − 20.19), while the ASDR was 0.13 per 100,000 population (95% UI: 0.11−0.15), with an EAPC of −1.59 (95% confidence interval [CI]: −1.73 to −1.45), indicating a sustained decline in RA ASDR. The age-standardized DALYs rate was 34.54 per 100,000 population (95% UI: 23.90 − 48.67), with an EAPC of 0.15 (95% CI: 0.10 to 0.20). Regionally, high Socio-Demographic Index (SDI) regions exhibited the highest ASPR, ASIR, and age-standardized DALYs rates, suggesting a greater overall burden of RA. Interestingly, middle SDI regions showed the highest ASDR, potentially indicating differences in disease management and access to care that impact mortality despite a lower overall burden compared to high SDI regions. Decomposition analysis identified population growth as the primary driver of the increasing RA burden. Cross-national inequality analysis revealed that RA burden remains concentrated in high SDI countries, though overall health inequality has declined. Conclusions The substantial global burden and regional disparities of RA in the working-age population necessitate targeted interventions. High SDI regions require strategies focusing on early diagnosis and optimal management to reduce the high burden. Elevated mortality in middle SDI regions demands improved access to effective treatment. These findings underscore the need for SDI-tailored public health approaches to address the specific challenges in each context.